Neoproterozoic extension and the Central Iapetus Magmatic Province in southern Mexico: new U-Pb ages, Hf-O isotopes and trace element data of zircon from the Chiapas Massif Complex - Weber, Bodo; Schmitt, Axel Karl; Cisneros de León, Alejandro; González-Guzmán, Reneé; Gerdes, Axel (Gondwana research, 2020)
Final fragmentation of Rodinia occurred during the Ediacaran Period as Amazonia, Baltica and Laurentia drifted apart to form the Iapetus Ocean. Accompanying rift-related mafic dyke swarms of the Central Iapetus Magmatic Province (CIMP) were emplaced between 0.62 and 0.55 Ga, which are preserved in Laurentia and Baltica, whereas no coeval mafic rocks are known from Amazonia. First evidence for the CIMP extending into Oaxaquia (Rodinia-type basement of Mexico) was reported as tholeiitic dykes that intruded the Novillo gneiss, NE Mexico, at 619 ± 9 Ma. In Chiapas, SE Mexico, amphibolite dykes that are chemically similar to the Novillo dykes intruded anorthosite and gneiss. In this paper, a new dating approach to obtain mafic dyke intrusion ages is presented by targeting contact metamorphic zircon with the UPb method, employing Secondary Ion Mass Spectrometry. Zircon that crystallized in anorthosite at intrusive contacts to mafic dykes and at temperatures exceeding 700 °C (Ti-in-zircon thermometry) yields ages between 615 ± 7 Ma and 608 ± 12 Ma, reflecting the time of dyke intrusion. Zircon chemical and isotopic (Hf, O) characteristics suggest a diachronous sequence of metamorphic processes involving Zr release from FeTi oxides, breakdown and recrystallization of other phases, and fluid-mitigated reactions during Ordovician metamorphism. Zircon δ18O values of granulites from Oaxaquia range from +6.2‰ to +9.8‰, whereas Tonian (~0.92 Ga) metamorphic zircon from SE Chiapas yielded low δ18O values from +2.0‰ to +2.8‰ that are explained by the reactivation of major tectonic boundaries during Tonian gravitational collapse. The observations increase the known extent of the CIMP in Mexico, suggesting that a Neoproterozoic superplume was still active during the Early Ediacaran producing a Large Igneous Province that extended over Amazonia, Baltica and Laurentia. The results further suggest that Oaxaquia at the northern edge of Amazonia formed the conjugate margin of Baltica during rifting.
Gesehen am 25.01.2021